Assessment of the Countries’ Readiness to Detect and Control Cholera Outbreaks in the WHO African Region - Sodjinou, Vincent Dossou; Keita, Mory; Chamla, Dick; Kimenyi, Jean Paul; Braka, Fiona; Talisuna, Ambrose; Lata, Harsh; Mbayo, Guy; Kapaya, Fred; Mlanda, Tamayi; et al. (Archives of Clinical and Biomedical Research, 2022)
Objective: This study assessed the countries’ readiness to prevent, detect, respond and recover from cholera outbreaks. Methods: This descriptive and cross-sectional study targeted 28 countries at risk of cholera. A readiness tool, covering all pillars required by the global health security was developed. Criteria, fit-tested with the regional framework for cholera elimination by 2030, were defined for each pillar. Based on experts’ opinion, each pillar and corresponding criteria were weighted. Data was collected in each country through group discussion of multi-sectoral cholera teams. The data collected were analyzed and visualized through an online Power BI tool. The readiness for each pillar was rated good if the pillar assessment result reached at least 80 % of expected points. The readiness was moderate if ranging between 50 % and 80 %. The readiness was limited if the rating was below 50%. The readiness status of each country was based on the same criteria. Results: The overall countries’ readiness level to detect and respond to cholera was insufficient. Of the 23 responding countries, there was no country with good readiness. Seven countries had moderate readiness while sixteen had limited readiness level. Laboratory was the best performing pillar with good readiness reported in eight countries. Only three countries had good readiness level for surveillance, two countries for infection prevention and control, and one country respectively for coordination and, water sanitation and hygiene. Conclusion: Countries in the WHO African Region were not adequately prepared to prevent or control cholera outbreak. Such readiness assessment provided critical information about areas of improvement across the 11 pillars and should be regularly undert